Types of Migrant Bird Stay in the Area Coastal Beach City Banda Aceh - Khairunisak Khairunisak; Abdullah Abdullah; Ismul Huda; Khairil Khairil; Asiah MD (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
AbstractThe coast of Banda Aceh City is one area that is often visited by migratory birds with different types of habitats. This study aims to obtain data and information on the types of migratory birds and the types of habitats used by migratory birds on the coast of Banda Aceh City. Data collection is carried out to January 2022. The method used is direct observation with point counts. The parameters in this study are the types of migratory birds and the type of stopover habitat on the coast of Banda Aceh City. Based on research conducted on the coast of Banda Aceh City, it was found that the types of migratory birds that stopped by were Ardea Cinerea, Egretta alba, Egretta garzetta, Pluvialis fulva, Hirundo rustica, Sterna sumatrana, Merops philippinus, Numenius aquarta, Actitis hypoleucos, Nisaetus cirrhatus, Haliastereetus , and Butorides striata. From the results of the study, it can be concluded that there are 12 species of miran birds that stop on the coast of Banda Aceh City with coastal habitat types, mangrove forests, ponds, and swamps.Keywords: distribution, migratory birds, coastAbstrakPesisir pantai Kota Banda Aceh merupakan salah satu kawasan yang sering disinggahi oleh burung migran dengan jenis habitat yang berbeda. Penelitian ini bertujuan untuk memperoleh data dan informasi jenis burung migran serta jenis habitat yang digunakan burung migran di pesisir pantai Kota Banda Aceh. Pengumpulan data dilakukan pada bulan Januari 2022. Metode yang digunakan adalah observasi langsung dengan point count. Parameter dalam penelitian ini yaitu jenis burung migran dan jenis habitat persinggahannya di pesisir pantai Kota Banda Aceh. Bedasarkan penelitian yang dilakukan di pesisir pantai Kota Banda Aceh diperoleh hasil jenis burung migran yang singgah yaitu Ardea Cinerea, Egretta alba, Egretta garzetta, Pluvialis fulva, Hirundo rustica, Sterna sumatrana, Merops philippinus, Numenius aquarta, Actitis hypoleucos, Nisaetus cirrhatus, Haliaeetus leucogaster, dan Butorides striata. Dari hasil penelitian dapat disimpulkan jenis burung miran yang singgah di pesisir pantai Kota Banda Aceh sebanyak 12 spesies dengan jenis habitat pantai, hutan manggrove, tambak, dan rawa.Kata kunci: sebaran, burung migran, pesisir